Imagens Poéticas da Cultura Popular do Nordeste na Dramaturgia de Joaquim Cardozo - Santos, Paulo Henrique dos (2023)
This research focuses on the study of the dramaturgy of Joaquim Cardozo, more specifically, the plays O coronel de Macambira: Bumba-meu-Boi (1963) and De uma Noite de festa (1971), with the aim of studying the representations of poetic and archetype images of popular festivals in the Brazilian Northeast region that are present in the author's dramaturgy, either as a theme or as a space-time construction that encompass the configuration of the characters. Theatrical symbols are endowed with a specific language, that have multiple meanings and artistic-cultural phenomena that describe the history of the people in those regions, their beliefs and their desires, as well as the artistic production of Cardozo, who, through a unique poetry, places on stage the popular culture of the Brazilian Northeast region. The analysis of the dramaturgical texts is based on bibliographic studies by the author and other researchers who have also been interested in Cardoz's production. The research is anchored in the authors Câmara Cascudo (1978), Mário de Andrade (1982), Luiz Maurício Britto Cavalheira (2011) and Mikhail Bakhtin (2010), among others. Also considered are studies by Maria da Paz Ribeiro Dantas (2003), João Denys Araujo Leite (2017) on the author's biography, his poetic work and his immersion in the contemporary world. The work is developed from the precepts of comparative literature in the sense of Tânia Carvalhal (2003, 2006) and other theorists of comparative studies and studies on dramaturgy.